Complementary, alternative, and integrative medicine researchers' practices and perceived barriers related to open science: An international, cross-sectional survey. - Jeremy Y Ng; Lucas J Santoro; Kelly D Cobey; Amie Steel; Holger Cramer; David Moher (PLoS ONE)
Introduction and objective Open science (OS) aims to make the dissemination of knowledge and the research process transparent and accessible to everyone. With the increasing popularity of complementary, alternative, and integrative medicine (CAIM), our goal was to explore what are CAIM researchers' practices and perceived barriers related to OS. Methods We conducted an anonymous online survey of researchers who published in journals listed in Scopus containing the words "complementary", "alternative", or "integrative" medicine in their names. We emailed 6040 researchers our purpose-built electronic survey after extracting their email address from one of their publications in our sample of journals. We questioned their familiarity with different OS concepts, along with their experiences and challenges engaging in these practices over the last 12 months. Results The survey was completed by 392 researchers (6.5% response rate, 97.1% completion rate). Most respondents were CAIM researchers familiar with the overall concept of OS, indicated by those actively publishing open access (OA) (n = 244, 76.0%), registering a study protocol (n = 148, 48.0%), and using reporting guidelines (n = 181, 59.0%) in the past 12 months. Preprinting, sharing raw data, and sharing study materials were less popular. A lack of funding was reported as the greatest barrier to publishing OA by most respondents (n = 252, 79.0%), and that additional funding is the most significant incentive in applying more OS practices to their research (n = 229,72.2%). With respect to preprinting barriers, 36.3% (n = 110) participants believed there are potential harms in sharing non-peer-reviewed work and 37.0% (n = 112) feared preprinting would reduce the likelihood of their manuscript being accepted by a journal. Respondents were also concerned about intellectual property control regarding sharing data (n = 94, 31.7%) and research study materials (n = 80, 28.7%). Conclusions Although many participants were familiar with and practiced aspects of OS, many reported facing barriers relating to lack of funding to enable OS and perceived risks of revealing research ideas and data prior to publication. Future research should monitor the adoption and implementation of OS interventions in CAIM.